2021
DOI: 10.3389/fpls.2021.721681
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Metabolome and Transcriptome Reveals Insights for Cold Tolerance in Rapeseed (Brassica napus L.)

Abstract: Rapeseed (Brassica napus L.) is an important oilseed crop in the world. Its productivity is significantly influenced by numerous abiotic stresses, including cold stress (CS). Consequently, enhancement in CS tolerance is becoming an important area for agricultural investigation and crop improvement. Therefore, the current study aimed to identify the stress-responsive genes, metabolites, and metabolic pathways based on a combined transcriptome and metabolome analysis to understand the CS responses and tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 111 publications
2
57
0
Order By: Relevance
“…Rapeseed is an allotetraploid crop that practices broad genome replication and combination activities ( Song et al, 2020 ). Nevertheless, rapeseed yield is pretentious by numerous environmental factors such as cold, heat, drought, salinity, and heavy metals toxicity ( Raza et al, 2021a ; Raza et al, 2021b ; He et al, 2021 ; Raza, 2021 ; Su et al, 2021 ). The TCP TFs are antique plant-specific proteins ( Cubas et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rapeseed is an allotetraploid crop that practices broad genome replication and combination activities ( Song et al, 2020 ). Nevertheless, rapeseed yield is pretentious by numerous environmental factors such as cold, heat, drought, salinity, and heavy metals toxicity ( Raza et al, 2021a ; Raza et al, 2021b ; He et al, 2021 ; Raza, 2021 ; Su et al, 2021 ). The TCP TFs are antique plant-specific proteins ( Cubas et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenylalanine ammonia-lyase (PAL) produces precursors of various secondary metabolites, including lignin, phytoalexin, and phenolic compounds. This gene family is also associated with the production of the first enzyme of the phenylpropanoid pathway [1][2][3]. PAL genes have a molecular mass in the range of 270-330 kilodalton (kDa) and are present in higher plants, yeast, some bacteria, and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…The term transcriptomics refers to a set of techniques that are used to study the RNA transcripts in an organism. Several transcriptomic techniques are widely used to measure the abundance of the transcripts of interest ( Lowe et al, 2017 ; Mehmood et al, 2021 ; Raza et al, 2021c ). Studies have shown that stress-induced changes in gene expression may lead to the synthesis of novel proteins, stress mediating metabolic compounds, or encode transcription factors (TFs), which help to regulate the stress-responsive genes ( Table 4 ).…”
Section: Seven-(omics)-based Approaches To Improve Toxic Metals/metalloids Tolerance In Plantsmentioning
confidence: 99%